ETNOMATEMATIKA JEMBATAN EFEKTIFITAS IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS KONSTRUKTIVISME PADA KURIKULUM 2013 - Nandang Arif Saefuloh; Lilim Halimah (Universitas Islam Nusantara, 2021)
The implementation of constructivism learning goes wrong when an important part of it is forgotten, namely Scaffolding which should be integrated in every constructivism-based learning, and one form of Scaffolding is to apply ethnomathematics in its implementation, so ethnomathematics can be a bridge to achieve constructivism-based learning effectiveness.